Analisis Sistematika Metode Jarimatika Dalam Meningkatkan Keterampilan Perkalian Matematika Siswa di SD /MI - Khusnul Khotimah; Ninin Fitria; Intan Alif Cahayani, Intan Alif Cahayani; Juhji Juhji (PGSD FKIP UPR, 2024)
Mathematics education at the elementary level faces challenges in increasing students' understanding of mathematical concepts, including multiplication. Mathematics is considered by elementary school students to be a difficult, boring and monotonous subject. The mathematics learning method can be used to teach mathematics to students in a simple and easy to use way. This research aims to evaluate the effectiveness of the jarimatika method in improving students' multiplication numeracy skills in elementary schools. This research uses qualitative research methods with a literature study approach collecting data from seven relevant articles about the mathematics method in teaching mathematics in elementary schools. The findings show that the application of the jarimatika method consistently improves students' multiplication numeracy skills, with an increase in average scores of up to 62% - 85%. Using the jarimatika method can be an effective solution in improving the quality of mathematics education at the elementary level, as well as providing direction for the development of more innovative and effective learning methods.